Asphalt Pavement Mechanical Response of Accelerated Pavement Testing in Single-Axle and Dual-Axle Loading Modes - Zhiguang Guan; Chuanyi Zhuang; Peng Zhang (Advances in Civil Engineering)
The objective of this study is to evaluate the influence of moving loads on the asphalt pavement in response to single-axle and dual-axle loading modes using the full-scale accelerated pavement testing (APT) facility from Shandong Jiaotong University. First, a test lane of pavement with four structures is constructed. Eleven strain sensors and four pressure cells are embedded at different depths and positions. Secondly, a research on the strain and stress in single-axle and dual-axle loading modes is conducted. Finally, the time accumulation of strain and stress is defined to describe the degree of pavement damage. The study reaches the following conclusions: (1) the strain reversal is induced as the wheels pass through the pavement, and the stress is always a positive value. (2) Both the strain and the stress increase as the loading increases regardless of the loading modes. (3) Comparing the two loading modes at the same velocity and loading, the horizontal tensile strain peak, the horizontal compressive strain peak, and the stress peak are all greater in the single-axle loading mode. But the degree of pavement damage is greater in the dual-axle loading mode based on the points of the time accumulations of strain and stress of each pass.